(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Animal colours and patterns have typically been the subject of genetic and evolutionary research. Nevertheless, until relatively recently, the majority of research on the genetic foundation of animal pigmentation was conducted on model species, ignoring non-model species or relying mainly on candidate methodologies to acquire knowledge. With the development of high-throughput sequencing technology, it is now feasible to overcome previous limitations and open up new avenues for examining the genetic basis of animal coloration in a greater variety of species and colour characteristics. These technologies also enable us to investigate the broader relevance of different genetic structures and how they have affected the evolution of colour. In this study, we point out areas where understanding the biology and evolution of animal coloration gaps could be greatly aided by genome-wide research. Animal colouring research has made rapid use of new genomic methods, but there is still a long way to go before we can account for a wider range of species and colour features, including those with continuous variation or those depend on reflecting surfaces. We state that there has to be a concerted effort to confirm the functional importance of the genes and variations found using genome-wide approaches if we are to make any headway in comprehending animal colours.